BUDAYA HUKUM PENAMBANG TIMAH INKONVENSIONAL (TI) TERHADAP MEKANISME PERIZINAN BERDASAR PERDA PENGELOLAAN PERTAMBANGAN UMUM DI PROPINSI KEPULAUAN BANGKA BELITUNG - Derita Prapti Rahayu (Faculty of Law, Universitas Diponegoro, 2012)
Abstract Legal culture as themes middlemost for the possibility to know law in a realistic manner, so that it can be known whether law it is used or not. Research using socio-legal research finds The cause of the tin miners inkonvensiinal ( ti ) did not carry out the mechanisms of permit as specified in regulations island province of Bangka Belitung on the management of public mining because mechanism that are entailed must be shaped local-state ( cv )and partnering, cause the cost and time and ignorance them with a mechanism permit. Culture law tin miners inkonvensional ( ti ) against a mechanism based perda minimarkets mining common in the province of management kepulauan bangka belitung because the knowledge and perception of public opposition to the perda, because in terms of economy, education and knowledge of the mechanisms of licensing, that is largely not aware of the bureaucracy and the licensing procedure because it their education that low. arrangements are time consuming, whereas they mine a site just for a while when it's finished they moved, the behavior